Detection of uveal melanoma using fuzzy and neural networks classifiers - Daniel F. Santos; Helbert Eduardo Espitia (Universitas Ahmad Dahlan, 2020)
The use of image processing is increasingly utilized for disease detection. In this article, an algorithm is proposed to detect uveal melanoma (UM) which is a type of intraocular cancer. The proposed method integrates algorithms related to iris segmentation and proposes a novel algorithm for the detection of UM from the approach of fuzzy logic and neural networks. The study case results show 76% correct classification in the fuzzy logic system and 96.04% for the artificial neural networks.